2018
DOI: 10.5812/mejrh.64507
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Decreases Biomarkers of Inflamation (C-Reactive Protein and Erytrocyte Sedimentation Rate) and Improves Pain, Function and Quality of Life in Knee Osteoarthrtitis Patients: A Before-and-After Study and Review of the Literature

Abstract: Objectives: The aim of this study was to evaluate if ozone is capable of decreasing biomarkers of inflammation (CRP/ESR) and pain, and to improve function and quality of life in knee osteoarthrtitis (OA) patients. Methods: A prospective quasi experimental (before-and-after study) research was performed to investigate the effect of Ozone therapy protocol. The intervention included 4 sessions (1 session/week) of an intra-articular infiltration of a medical mixture of Oxygen-Ozone (95% to 5%) at 20 ug/mL concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Ozone (O 3 ), a gas discovered in the mid-19th century, is a molecule consisting of 3 atoms of oxygen in a dynamically unstable structure due to the presence of mesomeric states. 9 Intra-articular administration of an adequate mixture of oxygeneozone is supposed to reduce pain, to have protective immunomodulatory effects on cartilage, and to reduce oxidative stress, thus potentially representing an alternative to other injective methods 10 ; several researchers worldwide and many years of clinical experience have indicated that O 3 has the capacity to modulate inflammation. 2 It is highly reactive and, when injected into a joint capsule, it is able to stimulate fibroblastic joint repair, reduce inflammation, and may promote new cartilage growth.…”
Section: See Commentary On Page 287mentioning
confidence: 99%
“…Ozone (O 3 ), a gas discovered in the mid-19th century, is a molecule consisting of 3 atoms of oxygen in a dynamically unstable structure due to the presence of mesomeric states. 9 Intra-articular administration of an adequate mixture of oxygeneozone is supposed to reduce pain, to have protective immunomodulatory effects on cartilage, and to reduce oxidative stress, thus potentially representing an alternative to other injective methods 10 ; several researchers worldwide and many years of clinical experience have indicated that O 3 has the capacity to modulate inflammation. 2 It is highly reactive and, when injected into a joint capsule, it is able to stimulate fibroblastic joint repair, reduce inflammation, and may promote new cartilage growth.…”
Section: See Commentary On Page 287mentioning
confidence: 99%
“…Secondly pable of decreasing laboratorial biomarkers of inflammation; namely, C-reactive protein, erythrocyte sedimentation rate, and serum uric acid in 33 patients with knee OA (9). Ozone was both capable of decreasing inflammation biomarkers and improving clinical symptoms (pain, function, stiffness, and quality of life) in a two-month follow-up period, and with a level of significance of P < 0.05 (9).…”
Section: Argumentsmentioning
confidence: 96%
“…The arguments of this article are based on three previous quasi-experimental before-and-after studies published by the study group and with a level of evidence 2b (6,9,10). Scientists are encouraged to replicate the current promising findings for the management of knee OA.…”
Section: Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the management of knee osteoarthritis, it is necessary to use biomarkers for the diagnosis, monitoring, and progression of the disease. These biomarkers should evaluate clinical (pain, stiffness, function), biochemical (C-reactive protein, erythrocyte sedimentation rate, uric acid, interleukins), and radiological (minimal femorotibial joint space) results [6,7].…”
Section: Introductionmentioning
confidence: 99%